Mucoepidermoid variant of adenosquamous carcinoma arising in ovarian dermoid cyst: a case report and review of the literature. (1st January 2006) - Karateke, A.; Gurbuz, A.; Kir, G.; Haliloglu, B.; Kabaca, C.; Devranoglu, B.; Yakut, Y.
Abstract : A 40-year-old woman with mucoepidermoid variant of adenosquamous carcinoma arising in dermoid cyst in left ovary is presented. The patient was staged as IC. Total abdominal hysterectomy, bilateral salpingo-oophorectomy, omentectomy, and pelvic and para-aortic lymph node sampling were carried out. The disease recurred in postoperative 12th month. To our best knowledge, this is 12th case of adenosquamous carcinoma in dermoid cyst and third case of mucoepidermoid variant of adenosquamous carcinoma in the literature.